Gamifying textbook lessons with phonics for five-year-old learners at Fantasias Infantiles private school. - Lullwitz Zavala, Maria de Lourdes (2022)
This research work looks into the gamification of textbook lessons with phonics for young learners as a way of complementing their learning process at school. Several authors stress the importance of using innovative materials to supplement classroom learning. The main objective of this work was to complement the class textbook by suggesting additional materials and resources, specially for teaching phonics to young learners. To achieve the latter, it was necessary to measure students’ phonological awareness, which was carried out through a test. Then the English teacher and the coordinator were interviewed about teaching phonics. They were asked if they agreed these resources were necessary and if they considered gamification a beneficial method for their students. Finally, a survey was given to the teacher and the coordinator regarding their views about the proposal put forward, which consists of lesson plans where games are included to complement the English textbook. Both teacher and coordinator showed a positive attitude towards this gamification method to teach phonics to young learners. They recognized the positive impact that their students and school would achieve through the implementation of the suggested complementary materials.